Characterization of Finnish Borrelia burgdorferi sensu lato isolates by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and with monoclonal antibodies. - Tuomi, J (1995)
Thirty-seven Borrelia burgdorferi strains, isolated in 1992 from Ixodes ricinus in Finland, were investigated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and by immunoblotting and indirect immunofluorescence assay (IFA) with five to nine monoclonal antibodies (MAbs). By SDS-PAGE results and reactivities to MAbs H3TS, J 8.3, I 17.3, and D6, the 37 isolates were assigned to the species B. burgdorferi sensu stricto (n = 7), Borrelia afzelii (n = 17), or Borrelia garinii (n = 13). Twenty more isolates examined only by IFA and with part of the MAbs were distributed as follows: 9 B. burgdorferi sensu stricto and 11 other species. Among 16 of 37 isolates displaying a SDS-PAGE patterns considered typical of that of B. garinii, 3 were negative by the test with MAb D6; the rest were positive. The three MAb D6-negative isolates reacted with MAb J 8.3 but not with MAb I 17.3. It is suggested that these isolates of a previously undescribed type represent atypical B. afzelii strains deficient in the expression of OspB proteins. The misleading species designation by the SDS-PAGE result is described. The IFA results were generally consistent with those obtained by immunoblotting. The exception was for 3 of 29 isolates that were positive with MAb H5332 by immunoblotting but that were IFA negative. In the present material of 57 strains, all 16 B. burgdorferi sensu stricto isolates originated from the Aland Islands. B. afzelii and B. garinii were isolated from all three regions where ticks were collected. The distributive difference seems to offer a basis for comparative clinico-epidemiological studies of Lyme borreliosis.